Neuroprobability: the Janus probability third face in court - Andrade, M.; Ferreira, M. A. M.; Filipe, J. A.; Coelho, M. P. (IIOAB Journal, 2013)
Usually the probability theory is approached from a purely mathematical viewpoint or, not entirely in alternative, from a philosophical perspective. If one confines to the mathematical perspective, probability” must be seen as a primitive concept, in a Kolmogorov sense. To discuss the content of the concept, a more comprehensive framework of the Knowledge Theory is needed. In this paper it is intended to present another approach based on the concepts that are typical of Neuroeconomics, that go beyond the rationality either quantitative or qualitative. This may be described simply by the word “Neuroprobability”. Reflections in the notion of probability, which began with questions related to hazard games problems, allowed a much more simplified approach in many problems that arise every day. But the emergence of different approaches, different schools, and the debate around it suggests that different scenarios allow different mind moves. The epistemological approach is supported following the subjective notion of probability, but not entirely denying that in certain phenomena another one may be adopted. And often some decisions about random events are taken in the form of pure reactions, not supported for any kind of reason, as it happens for example in Neuroeconomics, giving rise to what we may call a different concept of probability, the Neuroprobability.